PENERAPAN MODEL PROBLEM BASED LEARNINGUNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMP - Nurbaiti Nurbaiti; Edy Tandililing; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe study examined the effect of  problem based learning model  to improve student learning outcomes in work and  simple plane. The method of this research was pre-experimental design with one group pretest-posttest. The sample was  31 students of VIII C grade SMPN 17 Pontianak for participan which has taken by purposive sampling technique. The instrument used multiple choice with 20 question . Learning outcomes from the usage of problem based learning model before being applied (pretest) with an average score of 46.30 on low category. The posttest obtained an average score of 57.42% on medium category. It improved on medium category with N-gain  10.47. The results of using the problem based learning model in improving learning outcomes based on pretest and posttest using the Kolmogrov Simornov test showed a significant difference. The effectivity of this problem based learning modelis 0.67(medium level). The results of this study are expected to be an alternative in an effort to improve student learning outcomes by using a problem based learning model. Keywords: Problem Based Learning Model, Learning Outcome, Work and  Simple Plane